سیرت طیبہ صلی اللہ علیہ وآلہ وسلم کا عدلیاتی پہلو: ایک تحقیقی جائزہ: A Research Review of the Prophetic Justiceﷺ - Fareed ud din, Hafiz; Ahmad, Sheraz (Al-Amīr Research Journal for Islamic Studies, 2021)
Islam is a religion of peace and it has provided a strong system of justice for the establishment of peace and order, the practical picture of which is available to the Muslim Ummah in the form of Sira-e-Taiba of the Holy Prophetﷺ. On which the seal of beauty has been recorded by Allah Himself. Therefore, the system of justice of Islam can be used only when the solution of all issues is sought from Sira-e-Taiba because Heﷺ has eliminated the distinction between rich and poor in the supremacy of law. The Holy Prophet ﷺ has set great and enlightening examples of justice for humanity, the pursuit of which leads to peace and tranquility of social life. In his Supreme Court, the Qur'an and Sunnah and consensus and analogy were of fundamental importance. In the Qur'an and Hadith, Sira-e-Taiba had the status of Shāri' and Legislator, while in consensus and speculation, Sira-e-Taiba has promoted thinking and counseling. The center and axis of Islamic law is your caste. He ﷺ has established justice, supremacy, and law in every field of worship, affairs, disputes, and crime. Therefore, in this article, the judicial aspect of His ﷺ Sira-e-Taiba has been explained in the light of the Qur'an and Hadith, the Sahabah and the followers, and the edicts of the Imams and jurists.